2021
DOI: 10.1007/s10900-021-00984-3
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Extent of COVID-19 Vaccination Hesitancy in Healthcare Workers

Abstract: COVID-19 vaccines were approved in late 2020 and early 2021 for public use in countries across the world. Several studies have now highlighted COVID-19 vaccination hesitancy in the general public. However, little is known about the nature and extent of COVID-19 vaccination hesitancy in healthcare workers worldwide. Thus, the purpose of this study was to conduct a comprehensive worldwide assessment of published evidence on COVID-19 vaccine hesitancy among healthcare workers. A scoping review method was adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
508
11
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(584 citation statements)
references
References 48 publications
52
508
11
13
Order By: Relevance
“…The concerns cited by the respondents with regard to the COVID-19 vaccines were largely shared with participants in other studies [16][17][18]24]. To counteract these concerns, it may be helpful to highlight what is known so far about the adverse effects of COVID-19, so that people can weigh the risks and benefits of vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concerns cited by the respondents with regard to the COVID-19 vaccines were largely shared with participants in other studies [16][17][18]24]. To counteract these concerns, it may be helpful to highlight what is known so far about the adverse effects of COVID-19, so that people can weigh the risks and benefits of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review of vaccination willingness among HCWs shows that an average of 22.5% refuse to be vaccinated against COVID-19 or remain hesitant. Concerns about the safety, efficacy, and side effects of the coronavirus vaccines were the most common reasons for hesitating or refusing immunization [ 17 ]. In addition, individuals who reported having been vaccinated against influenza in the past were more likely to be vaccinated against COVID-19 [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trust in vaccines, positive emotions, and locus of control were high predictors of recommendation; some research has shown that age, as a factor capable of affecting perceived risk, inversely influences fear and hesitation in vaccines in healthcare personnel [27][28][29]; however, the results on the present sample confirmed a more positive perception and greater confidence in the vaccines of younger healthcare professionals [30]. Future research will have to clarify exactly the role of age concerning the various variable trusts, recommendations, hesitancy, and fear for vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted that COVID-19 vaccine hesitancy among the public could be a potential threat to global public health [5][6][7][8][9]. However, little is known about the reasons and factors behind vaccine hesitancy in the Saudi population.…”
Section: Introductionmentioning
confidence: 99%